Indium catalyzed Friedel-Crafts benzylation of aromatic compounds with benzyl halides - Keum, GC; Lim, HJ; Kang, SB; Kim, YS; Chung, BY (KOREAN CHEMICAL SOC, 2000)
Treatment of the aromatic compounds with benzyl halides in the presence of a catalytic amount of indium gave the corresponding diarylmethane products in good to excellent yields.
Keywords: ALKYLATION; SUBSTITUTION; CHEMISTRY; REAGENT; TOLUENE; ARENES; METAL